Analysis of Service Quality Improvement at PT XYZ through the Integration of the Kano Model, Markov Model, and the Push–Pull–Mooring Effect - Rangga Garnama; Eko Rudi Cahyadi; Alim Setiawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Increasing competition in the pest control service industry requires companies to improve service quality while maintaining customer retention. This study aims to analyze service quality attributes, factors influencing switching intention, and their implications for customer retention at PT XYZ through the integration of the Kano Model, Push–Pull–Mooring (PPM) framework, and Markov Model. A quantitative approach was employed using survey data collected from 385 PT XYZ customers who had used the company’s services for at least one year. The results indicate that PT XYZ’s service attributes are classified into 21 Must-Be attributes, 11 One-Dimensional attributes, and 14 Attractive attributes. Attributes related to responsiveness, communication, work monitoring, and customer comfort were identified as having the greatest potential to enhance customer satisfaction. The PPM analysis shows that push effect is at a low level, pull effect is at a moderate level, while mooring effect is the most dominant factor in retaining customers. Consequently, customers’ switching intention remains low. Furthermore, the Markov Model analysis indicates that PT XYZ has a customer retention probability of 71% and is projected to maintain a market share of 41.5% under steady-state conditions. The findings demonstrate that successful customer retention is determined not only by the fulfillment of basic service requirements but also by the company’s ability to create added value, strengthen customer trust, and establish long-term relationships. The integration of the Kano Model, Push–Pull–Mooring framework, and Markov Model provides a comprehensive approach for developing sustainable service quality improvement and customer retention strategies in the pest control industry.